Juvenile and juvenile-onset systemic lupus erythematosus patients: Clinical characteristics, disease activity and damage - Rasha E. Gheith; Iman I. El-Gazzar; Hussein S. El Fishawy; Abeer M. Nour El-Din; Dina M.R. Bahgat; Tamer A. Gheita (SpringerOpen, 2017)
Background: The diagnosis of systemic lupus erythematosus (SLE) in children is challenging. The heterogeneous manifestations and disease impact on the child's growth highlight the importance of timely diagnosis and management. Objective: The aim of the work was to assess and compare the clinical characteristics, disease activity and damage between children with juvenile SLE (JSLE) and adult patients with juvenile-onset (JO-SLE). Patients and methods: 78 SLE patients; 26 children (JSLE) and 52 JO-SLE adults were included in this study. Disease activity was assessed using the SLE Disease Activity Index (SLEDAI) and organ damage using the Systemic Lupus International Collaborating Clinics (SLICC) index. Results: The mean age of the JSLE children was 13.25 ± 2.09 years and 23.17 ± 4.26 years for JO-SLE cases. Age at disease-onset and female gender tended to be higher in JO-SLE cases than in children with JSLE. There was a significantly higher frequency of serositis, nephritis and hematological involvement in the JO-SLE (57.7%, 76.9%, 73.1%, respectively) compared to the JSLE cases (15.4%, 30.8%, 30.8%, respectively) (p < 0.001 for all). The erythrocyte sedimentation rate, creatinine and proteinuria were significantly increased in JO-SLE while alkaline phosphatase was higher in JSLE cases. In JO-SLE cases, SLEDAI significantly increased (5.96 ± 6.18 vs 3.12 ± 1.97; p = 0.003) and the SLICC tended to increase compared to the JSLE children. More JO-SLE cases received hydroxychloroquine and azathioprine. Conclusion: The existence of differences in clinical phenotype has been confirmed, between JSLE and JO-SLE especially as regards serositis, nephritis and heamatological affection. The disease damage was comparable which denotes that the maximum organ involvement occurs in childhood with an almost stationary course.